Complication of treatment of carcinoma in situ of the bladder with photodynamic targeted cystodiathermy - Murtagh, K (Ann R Coll Surg Engl, 2014)
We report two cases of bladder contracture following photodynamic or ‘blue light’ detection and cystodiathermy for bladder carcinoma in situ. These patients were unsuitable for treatment with immunotherapy/chemotherapy or had disease recurrence following such treatment. Radical cystectomy was not a treatment option in either patient. Each underwent serial photodynamic cystodiathermy over a three-year period. Neither patient developed muscle invasive disease. However, treatment resulted in contracture of the bladder and incontinence of urine. Patients need to be fully aware of this potential complication in order to make informed choices about their care.